PELESTARIAN TEKA-TEKI PERIBAHASA BALI MELALUI GAME TRIVIA CECIMPEDAN BERBASIS MOBILE - Dewa Putu Yudhi Ardiana; I Wayan Dharma Suryawan (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThe phenomenon of the lack of use of Balinese language in Balinese communication has causedconcern and even fear of the use of Balinese as the language of Balinese communication will beextinct. Responding to these problems, the Government of Bali has to preserve Balinese culture. TheGovernment of Bali effort must be supported by the awareness of each Balinese community toconserve Balinese culture. The use of Balinese should be taught as early as possible to youngBalinese to get used to using Balinese. As a form of effort in introducing Balinese to the youngergeneration of Balinese, this study developed a mobile game with Balinese culture as a content. Thecontent presented in this game is Cecimpedan which is a Balinese proverb in the form of puzzle thatis traditionally played individually or in groups. Cecimpedan is useful for sharpening the mind andtesting the vocabulary of Balinese language. The results showed had successfully developed a triviagame application and trivia. The result of alpha testing conducted by media experts to test thefunctionality, efficiency, usability and portability of the game show that game was working asplanned.Keywords: Culture, Bali, Cecimpedan, Game, Mobile, TriviaABSTRAKFenomena kurangnya penggunaan bahasa Bali dalam komunikasi masyarakat Bali menyebabkankekhawatiran bahkan ketakutan penggunaan Bahasa Bali sebagai bahasa komunikasi masyarakatbali akan punah. Menanggapi permasalahan tersebut, Pemerintah Provinsi Bali telah berupaya untukmelestarikan budaya Bali. Upaya yang dilakukan Pemerintah Provinsi Bali harus didukung olehkesadaran tiap masyarakat Bali untuk berupaya melestarikan Bahasa Bali. Penggunaan Bahasa Baliharus sedini mungkin diajarkan kepada generasi muda Bali untuk membiasakan diri menggunakanBahasa Bali. Sebagai bentuk upaya dalam memperkenalkan Bahasa Bali kepada generasi muda Balimaka pada penelitian ini dikembangkan permainan digital (game) berbasis mobile dengan budayaBali sebagai isinya. Konten yang disajikan dalam permainan ini adalah cecimpedan yang merupakanperibahasa Bali berbentuk teka-teki yang secara tradisional dimainkan secara individual ataupunkelompok. Cecimpedan berguna untuk mengasah otak dan menguji pembendaharaan bahasa Bali.Hasil penelitian menunjukkan telah berhasil mengembangkan aplikasi game trivia cecimpedan.Melalui pengujian alpha testing yang dilakukan oleh ahli media untuk menguji functionality,efficiency, usability dan portability dari aplikasi game didapatkan hasil aplikasi game yangdikembangkan sudah bekerja sesuai dengan rancangan yang dibuat.Kata Kunci: Budaya, Bali, Cecimpedan, Game, Mobile, Trivia